An observational study on the perceptive and physiological variables during a 10,000-m race walking competition - Vernillo, G.; Agnello, L.; Drake, A.; Padulo, J.; Piacentini, M. F.; La Torre, A. (The Journal of Strength and Conditioning Research, 2012)
In this study, we observed the variations on physiological and perceptual variables during a self-paced 10,000-m race walking (RW) event with the aim to trace a preliminary performance profile of the distance. In 14 male athletes, the heart rate (HR) was monitored continuously throughout the event. The rating of perceived exertion (RPE) was collected using the Borg's 6-20 RPE scale placed at each 1,000 m of an outdoor tartan track. Pacing data were retrieved from the official race results and presented as percent change compared with the first split time. The athletes spent 95.4% at 90-100% of the HRpeak, whereas the other work (4.6%) was negligible. During the race, a shift toward higher HR values was observed because % HRpeak increased by 3.6% in the last vs. the first 1,000-m sector (p = 0.002, effect size [ES] = 1.55 ± 0.68, large). The mean RPE reported by the athletes in the last 1,000 m was significantly higher than in the first 5 sectors (p < 0.02, ES = 1.93-2.96, large to very large). The mean percent change increased between the first 6 sectors and the last 1,000-m sector (p < 0.01, ES = 1.02-2.1, moderate to very large). The analysis of walking velocity at each 1,000-m sector suggested the adoption of a negative pacing. In conclusion, the RPE may be a valid marker of exercise intensity even in real settings. Match physiological and perceptual data with work rate are required to understand race-related regulatory processes. Pacing should be considered as a conscious behavior decided by the athletes based on the internal feedback during the race.